2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--18421
|View full text |Cite
|
Sign up to set email alerts
|

Work in Progress: Analysis of Mobile Technology Impact on STEM-Based Courses, Specifically Introductions to Engineering in the Era of the iPad

Abstract: received his B.S. and Masters in Electrical Engineering from the University of Texas at El Paso with a special focus on data communications. He is currently pursuing a PhD in Electrical and Computer Engineering. Mr Perez has been teaching the Basic Engineering (BE) BE 1301 course for over 5 years. Lead the design for the development of the new BE course (now UNIV 1301) for engineering at UTEP: Engineering, Science and University Colleges. Developed over 5 new courses, including UTEP technology & society core c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In addition, where existing research into iPad impact on student performance does exist (e.g. Perez et al, 2011), our work is able to contribute a more nuanced measure of performance. Rather than seeing performance as a single or aggregate measure, this research distinguishes between the different kinds of learning demonstrable within the final exam and, through this sensitive measure, is better positioned to understand student performance in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, where existing research into iPad impact on student performance does exist (e.g. Perez et al, 2011), our work is able to contribute a more nuanced measure of performance. Rather than seeing performance as a single or aggregate measure, this research distinguishes between the different kinds of learning demonstrable within the final exam and, through this sensitive measure, is better positioned to understand student performance in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Though student perceptions and attitudes are well understood, the impact of tablet use in the classroom on student performance is poorly understood. One study shows that the tablet had no impact on student learning at all (Perez, Gonzalez, Pitcher, & Golding, 2011). A recent systematic review (Nguyen et al, 2015) shows existing studies of tablet use within the post-secondary education are typically exploratory, small in scale, or 'one-off' studies that are unclear as to the impact the device is having on learning.…”
Section: Understanding the Implications Of Tablet Adoption On Student Performancementioning
confidence: 99%
“…The tablet is a device that can foment greater student involvement (Diemer, Fernandez, & Streepey, 2012; Fontelo, Faustorilla, Gavino, & Marcelo, 2012). Nevertheless, Perez, Gonzalez, Pitcher, and Golding (2011), have found that tablet use among students does not substantially improve academic performance.…”
Section: Discussionmentioning
confidence: 99%